Challenging the claims on the potential of biochar to mitigate climate change. - RITTL, T. F. (2015)
Thesis (PhD) - Wageningen University, Wageningen. Promotors: T. W. Kuyper, E. Hoffland, B. J. M. Arts, Wageningen University. Co-promotor: Etelvino Henrique Novotny, CNPS.